A CASE STUDY OF REPORTING OF NEWSPAPER BH DANI DURING THE WAR IN BOSNIA - Ivica Mladenovic; Dragoljub Kaurin (Srpska Politička Misao)
The key idea of this article is to present a case study of reporting of newspaper BH Dani that were battling the dominant ethno-nationalist style of reporting. Methodologically speaking, this project uses content analysis and the process of developing and grouping the ideas is very important. War in Bosnia is the societal and political context of this research. A number of key authors that theorized the idea of propaganda and media influence on thinking and attitudes as well as persuasion is introduced to the reader in the first part of the article. The case study goes on to show how articles in BH Dani explored cases of intolerance of Bosnian government and war forces, their war atrocities and displayed writings where the war situation is presented objectively. The article is then concluded with the recapitulation of key ideas and also its contribution to knowledge is discussed.